Asylum in the EU: One of the Many Faces of Rule of Law Backsliding?. (9th September 2021) - Tsourdi, Evangelia (Lilian)
Abstract : EU values – Rule of law backsliding – Rule of law and fundamental rights interrelation – Refugee protection – Common European Asylum System – Implementation gap in asylum – Lack of fair responsibility sharing in asylum – Structural deficiencies in national asylum systems – Defiance of asylum obligations and the duty of sincere cooperation – Systemic fundamental rights violations – Upholding the rule of law – European Asylum System redesign – Systemic infringement actions – Rule of law monitoring